Pengaruh Budaya Kerja, Komitmen Tugas dan Komunikasi Kerja Terhadap Kinerja Pegawai Pada Dinas Kesehatan dan PBKB Kabupaten Lingga - Hasim, Hasim; Satifali, Utrika; Ardiansyah, Teuku Taufik; Syarini, Fitria (eScience Humanity Journal, 2024)
This research was conducted with the aim of understanding the influence of work culture, task commitment, and work communication on employee performance at the Health Office and PPKB of Lingga Regency. The total population in this study consists of all employees of the Health Office and PPKB of Lingga Regency, totaling 255 individuals. The sample size was determined using the Slovin formula, resulting in a sample of 156 respondents. The sampling technique is through probability sampling. Data collection was carried out by distributing questionnaires to the respondents. The collected data was processed using SPSS data processing software. The research findings indicate that work culture has an insignificant effect on employee performance, task commitment has a significant effect on employee performance, and work communication has a significant effect on employee performance. Simultaneously, it is known that work culture, task commitment, and work communication significantly influence employee performance. The adjusted R square value is 0.891 or 89.1%. This means that work culture, task commitment, and work communication can explain employee performance variables by 89.1%. Meanwhile, the remaining 10.9% is explained by other variables not included in this research model.